Vaginal Microorganism Pattern in Premature Rupture of Membrane: Pola Mikroorganisme Vagina pada Ketuban Pecah Dini - vanya vanesha; John J. E Wantania; Rudy A. Lengkong (Indonesian Socety of Obstetrics and Gynecology, 2021)
Objective: To determine the pattern of vaginal microorganisms in pregnant women and risk factors for premature rupture of membranes (PROM) in Manado.Methods: This is a case-control study. Samples was 40, divided into 20 pregnant with PROM and 20 control samples. Samples were taken from Kandou Manado Hospital and network hospitals within the inclusion criteria. Samples were taken from vaginal swab for microorganism culture.Results: The highest age distribution in the case of PROM was in the reproductive age group of 20-35 years, 19 people (95%, p = 1,000). Primiparas were dominant in the PROM were 11 people (55%, p = 0.204). The distribution of BMI mostly from the overweight and obesity groups of 11 people (55%, p = 0.527). In the PROM, 19 people (95%, p = 0.605) did not smoke. Escherichia coli was the most microorganisms in swab vaginal of PROM: 7 people (29.17%).Conclusion: The most microorganisms found in PROM are Escherichia coli, Enterobacter cloacae and Staphyloccocus aureus and in non-PROM are Klebsiella oxytoca, Staphylococcus epidermidis, Staphylococcus saprophyticus and Pseudomonas fluorescens. There was no relationship between BMI, age, parity, smoking, and gestational age with the incidence of PROM in this study.Keywords: PROM , vaginal microorganisms pattern, vaginal swab. Abstrak Tujuan: Untuk mengetahui pola mikroorganisme vagina pada kultur vaginal swab wanita hamil dan faktor risiko pada KPD di Kota Manado.Metode : Studi ini bersifat case control. Total sampling 40 sampel dibagi menjadi 20 sampel hamil dengan KPD dan 20 kontrol. Sampel diambil dari RSUP Kandou Manado dan RS jejaring yang memenuhi kriteria inklusi. Semua pasien dilakukan pengambilan sampel swab vagina untuk dilakukan kultur mikroorganisme.Hasil : Hasil sebaran usia pada KPD paling banyak pada usia reproduksi 20-35 tahun yaitu 19 orang (95%, p = 1,000). Primipara dominan pada KPD yaitu 11 orang (55%, p = 0,204). Hasil sebaran IMT paling banyak kelompok overweight dan obesitas yaitu 11 orang (55%, p = 0,527). Pada KPD sebanyak 19 orang (95%, p = 0,605) tidak merokok. Mikroorganisme terbanyak pada swab vagina KPD adalah Escherichia coli sebanyak 7 orang (29,17%). Kesimpulan: Mikroorganisme terbanyak pada KPD adalah Escherichia coli, Enterobacter cloacae dan Staphyloccocus aureus dan pada non KPD adalah Klebsiella oxytoca, Staphylococcus epidermidis, Staphylococcus saprophyticus dan Pseudomonas fluorescens. Tidak ada hubungan antara IMT, usia, paritas, merokok, dan umur kehamilan dengan kejadian KPD pada penelitian ini.Kata kunci: pola mikroorganisme vagina, ketuban pecah dini, swab vagina.